AKTUALISASI SILA KEMANUSIAAN YANG ADIL DAN BERADAB DI ERA REFORMASI - Aristin, Rini (Aspirasi: Jurnal Ilmiah Administrasi Negara, 2016)
Pancasila is the foundation and the Indonesian state ideology and also fuction at platform to interact in social life of nation and state. In this era began to lose his spirit of Pancasila sourced from Indonesian nation personality began to fade as result of misuse of the implementation of the values of Pancasila in the previous era and also the influx of an unstoppable globalization. Sila just  and civilied humanity contains a moral massage how shuold the Indonesian community honor, respect other humans (humanizing) in accordance with the dignity that has been mandated by the Pancasila. Concern the behavior of people are not in accordance with the values to be true not only in Indonesia bat also worrying the United State about same thing. That’s necesssary for the implementation of character education, not only through formal education but also through informal education.